Magnolia (2018)
"Magnolia, is a design strategy that is based on the Triple Helix concept, which seeks to integrate national and international capabilities of the State, Universities and private companies to generate a facilitating entrepreneurship environment for women, starting from the creation of a development plan divided into 5 stages described below: Sowing: Participatory socialization and public presentation of women seeking to link to the initiative. Irrigation: Training women to build an entrepreneurial profile that reinforces their initiatives and make them competitive. The harvest: Selection of women as representatives for competitions, assistants of entrepreneurs, or as new leaders for the future members. The sale: Exposure of successful initiatives to key actors to achieve support and investment. Pollination: Reinversion of knowledge, contributing to the linking of new members by exposing their success stories and actively collaborating in their training".-- Tomado del Formato de Documento de Grado.